Malay students' politeness strategies - Abdul Latif @ Bapoo, Lilisuriani; Mokhtar, Nor Zainiyah Norita (2013)
This study investigates how IIUM Malay tertiary learners’ pragmatic competence, specifically on how they apply politeness strategies in performing the speech acts of requests and persuasions is perceived. This study is based on Brown and Levinson’s (1978) politeness strategies where they concluded that even when there are broad, comparable linguistic strategies available in world languages, there are local cultural factors that may trigger universality of politeness. This was however commented by Grundy (2000) who stated that politeness is not equally distributed in all social and situational contexts and it is to a certain extent, a “term we use to describe the relationship between how something is said to an addressee and that addressee’s judgment as to how it should be said” (p. 164). Thus, this study aims to examine the strategies and discourse used by Malay students from International Islamic University Malaysia, and to discover if they are judged similarly by addressees of different background namely fellow Malay students, Malay lecturers of English and native English lecturers. The data were obtained from actual requests made through the short messaging system (SMS), a discourse completion test (DCT) on persuasive messages and Likert scaling.